Governance of Village-Owned Enterprises (BUM Desa) in Achieving Village Resource Independence in Bogor District - Kennedy, Posma Sariguna Johnson; Kusuma, Vincentius Andi Mintarja (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
Village-Owned Enterprises (BUM Desa) were established as instruments to enhance village resources, as mandated by Law No. 6 of 2014 on Villages. This study aims to analyze village potential, identify priority business areas for BUM Desa, and evaluate the governance practices implemented to support the economic independence of village resources. Adopting a descriptive qualitative approach, data was collected from both primary and secondary sources. The research focuses on BUM Desa entities within Bogor Regency, specifically BUM Desa Citra Wangi in Dramaga District, BUM Desa Sehati in Citeurep District, and BUM Desa Singasari Mandiri Energi in Jonggol District. The findings indicate that village potential identification was not fully aligned with local resource policies, particularly regarding the effective utilization of village assets and the empowerment of communities as economic drivers. Business priorities within BUM Desa often failed to focus on asset management, and governance practices lacked standardized guidelines and objective assessment measures. Additional issues included negative interventions by village heads, conflicts of interest among BUM Desa administrators, and low levels of community involvement, which hindered the effectiveness of BUM Desa in fostering economic independence.